An Integrated Approach Based on Fuzzy Ahp and Grey Relational Analysis for Heating Source Selection - Organ, Arzu; Yalçin, Engin (European Scientific Journal, ESJ, 2017)
Decision making has always been difficult for enterprises in an extremely competitive environment. It is one of the toughest decisions to select heating source source. It is difficult to take into consideration factors such as quality of energy source, pollution degree of environment, attainability, sustainability. Due to this hardship, Multi criteria decision making method is beneficial for solving such kind of problems. Grey relational analysis and fuzzy AHP are efficient methods of multiple criteria decision making. In this paper, the best heating source source selection has been carried out by fuzzy AHP integrated grey relational analysis. In the phase of determining criteria weights is used by fuzzy AHP, while determining ranking of alternatives, grey relational analysis is used. The criteria used in this study are ecofriendly level, cost, attainability, calorific value and process ability. The alternatives used in this study are coal, natural gas, diesel and electricity. Out comes show that Grey RelatÄ±onal AnalysÄ±s can be used successfully in the process of solving heating source selection problems